2017
DOI: 10.1128/jvi.02262-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hepatitis C Virus (HCV) Envelope Diversification from Acute to Chronic Infection within a Sexually Transmitted HCV Cluster by Using Single-Molecule, Real-Time Sequencing

Abstract: In contrast to other available next-generation sequencing platforms, PacBio single-molecule, real-time (SMRT) sequencing has the advantage of generating long reads albeit with a relatively higher error rate in unprocessed data. Using this platform, we longitudinally sampled and sequenced the hepatitis C virus (HCV) envelope genome region (1,680 nucleotides [nt]) from individuals belonging to a cluster of sexually transmitted cases. All five subjects were coinfected with HIV-1 and a closely related strain of HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
3
20
0
Order By: Relevance
“…PacBio single-molecule, real-time (SMRT) sequencing was performed on one to two samples before and after seroconversion in order to define the founder and evolving E1/E2 sequence variants. SMRT sequencing technology is coupled with circular consensus sequencing and was ideal for this analysis because it allowed the full-length envelope genes to be sequenced in a single read with minimal sequencing errors (23,24). The genetic diversity of E1/E2 quasispecies in each sample was determined from the predicted amino acid sequences by calculating the mean Hamming distance.…”
Section: Resultsmentioning
confidence: 99%
“…PacBio single-molecule, real-time (SMRT) sequencing was performed on one to two samples before and after seroconversion in order to define the founder and evolving E1/E2 sequence variants. SMRT sequencing technology is coupled with circular consensus sequencing and was ideal for this analysis because it allowed the full-length envelope genes to be sequenced in a single read with minimal sequencing errors (23,24). The genetic diversity of E1/E2 quasispecies in each sample was determined from the predicted amino acid sequences by calculating the mean Hamming distance.…”
Section: Resultsmentioning
confidence: 99%
“…The sequence data were generated by PacBio SMRT sequencing using stringent multiple passes to infer the circular consensus sequence (CCS) reads. This approach reduced the consensus sequence error rate from 1.6% to 0.4% and resulted in approximately 500 and 740 CCS reads per sample (11). Further information about the sequencing and individual samples can be found in C. K. Ho, et al (11).…”
Section: Sequence Datamentioning
confidence: 99%
“…(7)), but comparable studies for HCV are more challenging due to the high viral diversity observed during HCV infection, which makes it difficult to link infected individuals phylogenetically. In particular, there is a growing body of work indicating that within-host HCV diversity is maintained by multiple viral subpopulations with independent replication behaviour, where distinct long-lived lineages are intermittently detected in blood plasma over time (8)(9)(10)(11)(12). This observation implies that transmitted viruses are unlikely to be representative of the donor within-host HCV population sampled at a different point in time, and suggests there is potential for divergent viral strains to be transmitted from the same source individual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multitude of observational studies suggest that a substantial proportion of PWID carry mixed infections [18]. Furthermore, within-host evolutionary dynamics are complex [19][20][21][22][23][24][25][26]. Multiple co-existing lineages persist over time and are not necessarily detected at every sampling time [19,20,26], even using highthroughput sequencing [20,26], likely resulting from viral population structure [19,20,26,27].…”
Section: Introductionmentioning
confidence: 99%